A comparison of the positional effect of difluorination and the synergistic effect of siloxane-terminated side chains on benzodithiophene-based conjugated polymers for efficient photovoltaic application. Issue 18 (19th April 2022) - Wang, Qian; Hu, Zelong; Zhang, Lianjie; Qiu, Rihang; Zhou, Deng; Liang, Jiahao; Chen, Junwu
Abstract : The synergistic effect of siloxane terminus and difluorination is systematically studied through six polymer donors based on benzodithiophene and benzodithiophene-4, 8-dione. Abstract : Halogenation has been proved to be one of the most efficient chemical modification strategies to manipulate the energy levels and molecular assembly, while the study of the positional effect of halogen atoms for the polymer donor is limited. In this work, we systematically synthesized three wide bandgap polymer donors 35EH, 23EH and 26EH with 3, 5-, 2, 3-, and 2, 6-difluorobenzene groups in conjugated phenyl side chains, respectively. The controlled positions of the two fluorine atoms in conjugated side chains induced different steric hindrances in three polymer donors which significantly affected the optical bandgap, energy level, surface energy as well as the crystallization behavior. Due to the smaller steric hindrance and good crystallinity, polymer 35EH achieved high performance in polymer solar cells (PSCs) with power conversion efficiencies (PCEs) of over 11% when paired with acceptor IT-4F. Furthermore, by varying the alkyl side chain on the difluorobenzene to siloxane-terminated alkyl side chain, three relevant polymer donors named 35Si, 23Si and 26Si were synthesized. The introduction of the siloxane-terminated alkyl chain effectively enhanced the aggregation of 35Si and decreased the domain size in the blend film. As such, the 35Si:IT-4F based PSCs displayed the best PCE of 12.97%. Our work reveals that the combinatorial strategy of optimal difluorination and the siloxane-functionalized side chain could provide an effective pathway to modify the polymer properties for efficient photovoltaic application.